Assessment of SORL1 rare variants segregation in Alzheimer disease families and in vitro models suggests diverse penetrance and oligogenic inheritance: Genetics/genetic factors of Alzheimer's disease. (7th December 2020) - Nicolas, Gaël; Schramm, Catherine; Miguel, Laetitia; Lacour, Morgane; Rousseau, Stéphane; Wallon, David; Charbonnier, Camille; Zarea, Aline; Campion, Dominique; Rovelet‐Lecrux, Anne; Lecourtois, Magalie
Abstract: Background: SORL1 rare (allele frequency <1%) loss‐of‐function (LOF) and missense predicted damaging (Mis3) variants have first been identified in early‐onset Alzheimer disease (EOAD, onset before 66 years) patients with a positive family history. However, segregation data in families are still missing to assess the actual pattern of inheritance. Since then, we and others have shown an increased burden of SORL1 rare LOF and Mis3 variants in EOAD patients, whatever the family history, and in late onset AD patients, with a lower effect size. In addition, although the interpretation of the biological effect of LOF variants is rather straightforward, no formal evidence of a functional effect of Mis3 variants can be inferred from bioinformatics predictions only. Method: We gathered data from French families with a rare LOF or Mis3 variant and developed a cellular model to assess the role of SORL1 missense variants. Result: We studied 20 families with a LOF variant (mean age at onset (AAO) in probands, 55.4 years, range: [48‐65]). Seventeen showed a positive family history. Mean AAO in affected relatives was 66.3 (range: [50‐80]). One patient carried two LOF compound heterozygous variants. DNA was available in 18 relatives: 5/6 affected relatives carried the familial variant (AAO = [61‐78]) while 3/12 unaffected were also carriers, aged 42, 71 and 95, respectively. Strikingly, 57% affected carriers were APOE4+ including one homozygous, who was also a carrier of a LOF rare ABCA7 risk variant. We developed a functional assay using CRISPR/Cas9 introduction of variants in iPSCs. We succeeded in introducing a homozygous LOF variant showing increased levels of Aβ in the supernatant. We are now inducing neuronal differentiation and introducing missense variants to better sort missense variants for penetrance studies and understand mechanisms. Interestingly, in one family with a Mis3 variant associated with increased Aβ secretion, the proband was APOE4+ and carried a LOF rare ABCA7 risk variant. Additional families and variants are currently being studied. Conclusion: Our data support incomplete penetrance and oligogenic determinism in SORL1 families, making genetic counseling difficult. The development of cellular models will help us understand how and which missense variants result in reduced SORL1 functions.